Clinical Presentation of Patients with Aseptic Meningitis, Factors Influencing Treatment and Hospitalization, and Consequences of Enterovirus Cerebrospinal Fluid Polymerase Chain Reaction Testing - Glenn Patriquin; Jill Hatchette; Kevin Forward (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Clinical and laboratory features of enteroviral meningitis may overlap with those of bacterial meningitis. In the present retrospective review, we compared features of enteroviral (EV)-positive and -negative patients to determine those that were most influential in admission, discharge and in anti-infective administration.